Developing Crosslingual Ontologies in WissKI : Transcontinental Research Collaboration in the Africa Multiple Cluster of Excellence - Eisenhuth, Philipp; Fichtner, Myriel; Frede, Britta; Seesemann, Rüdiger (Modern Languages Open, 2023)
Since July 2019, the Africa Multiple Cluster of Excellence at the University of Bayreuth has been funding a project dedicated to the creation of an Islamic Cultural Archive (ICA), a database designed for collaborative research in English, French and Arabic connecting researchers based in Germany and four African countries. The ICA project pursues individual but interconnected studies revolving around Islamic learning in Africa. Supported by IT specialists, we develop a digital platform that meets the related requirements. The ICA seeks to develop new approaches to the handling of data through establishing an ontology-based digital research environment building on WissKI, a set of modules that extends the content management system Drupal with semantic web technology. The chapter sheds light on the technical implications of our endeavor to connect diverse alphabets and data from various digital and digitized media. The research team members connect their diverse data sets to create synergies between various research foci and interests, ranging from the nexus of Islamic knowledge production, dissemination, and acquisition to the socio-religious, political-economic, and cultural dimensions of Islamic learning. The chapter shows how our system allows us to collect and archive different types of data, generate metadata through an ontology, and connect data beyond language barriers. Most notably, our data description method links the data through multilayered and multilingual tags, as well as through comprehensive cross-references, thus constituting an innovative way of data handling that can benefit researchers in Islamic Studies as well as cultural and literary studies more broadly.